Дослідження генетичної мінливості генотипів Eleusine coracana (L.) Gaertn. та Eleusine indica (L.) Gaertn. за допомогою ISSR-аналізу - Баєр, Г.Я.; Пірко, Я.В.; Стаднічук, Н.О.; Рахметов, Д.Б.; Ємець, А.І.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2013)
Aims. The aim of investigation is the applicability of ISSR markers for uncovering polymorphism to study the relationships between Eleusine coracana and Eleusine indica genotypes. Methods. Eight genotypes were analyzed using four primers. Extracted DNA was successfully used for study by ISSR-PCR method. The genetic distances were used to construct the UPGMA dendrogram which characterized relationships between studied genotypes. Results. The level of genetic polymorphism of E. coracana is 81,5 % and E. indica – 75 %. The unique fragments have been revealed in 6 genotypes. The studied genotypes were divided in two clusters according their genetic background. Conclusions. It was shown that ISSR analysis is the useful method for fingerprinting and determination of relationships between the different E. coracana and E. indica genotypes.